An efficient approach of centroid alignment for spaceflight vehicles considering parameter uncertainties. (June 2022) - Liu, Jinguo; Chen, Keli; Wu, Chenchen; Wu, Guanglei
Abstract: This paper deals with centroid alignment for the spaceflight vehicles that work on orbit under microgravity environment, due to the unavailability of centroid measurement on ground, which is based on the principle of mass–radius products in different configurations of static equilibrium. A physical prototype of articulated mechanism for centroid alignment, consisting of three sets of linear modules with moving mass mounted, was developed and experimentally validated. The variational method was adopted to derive the error model for accuracy and sensitivity analysis of the developed articulated mechanism with the consideration of parameter uncertainties, from which it is found that the centroid position of the whole system is much more sensitive to the angular parameter variations than the linear ones. With the developed error model, an iterative approach of centroid alignment to ensure the centroid offset to meet the requirement is proposed, regardless of whether the parameter variations can be ignored, and numerous simulations verify the efficiency of the proposed approach. Highlights: A Cartesian-configuration mechanism for centroid alignment for spaceflight vehicles. Error modeling and analysis shows the sensitive factors influencing the accuracy. Centroid offset is sensitive to angular parameter variations in geometric dimensions. Verified efficient method for centroid alignment considering parameter uncertainties.